2001
DOI: 10.1021/bi010135x
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin, a Binding Protein with a Molten Globule-like Region

Abstract: Clusterin is a heterodimeric glycoprotein found in many tissues of the body and is the most abundant protein secreted by cultured rat Sertoli cells. The function of clusterin is unknown, but it has been associated with cellular injury, lipid transport, apoptosis, and it may be involved in the clearance of cellular debris caused by cell injury or death. Consistent with this last idea, clusterin has been shown to bind to a variety of molecules with high affinity including lipids, peptides, and proteins and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 76 publications
3
107
0
1
Order By: Relevance
“…Clusterin possesses molten globular-like structures that contain putative amphipathic ␣-helices (38). This structure allows clusterin to interact with the hydrophobic regions of many proteins exposed following stress (24).…”
mentioning
confidence: 99%
“…Clusterin possesses molten globular-like structures that contain putative amphipathic ␣-helices (38). This structure allows clusterin to interact with the hydrophobic regions of many proteins exposed following stress (24).…”
mentioning
confidence: 99%
“…It is known that the presence of intrinsic disorder can serve as one of the bottlenecks in structural characterization of a target protein that can affect several processes of the structure determination pipeline, such as expression and stability, 187,188 as well as solubility, 189,190 and predisposition for crystallization. 189,[191][192][193][194][195][196] In application to spondins and their partners, this hypothesis is supported by the observation that proteins with more predicted disorder typically have lower structure coverage. Data presented in our study revealed that spondins and their binding partners contain considerable levels of disorder and intrinsic disorder might be related to functionality of these proteins.…”
Section: Discussionmentioning
confidence: 93%
“…The primary structure of sCLU in both α-and β-chain subunits contains several large molten globule domains, amphipathic regions and coiled-coil α-helices [9,[33][34][35], which are typical of molecular chaperone -conformational adaptability to allow CLU protein to bind its substrate proteins or lipids with high affinity and low specificity [35][36][37]. Furthermore, one study has revealed that the glycosylation of sCLU may not be required for its overall secondary structure content and binding activity to its substrate [38].…”
Section: Biochemistry and Functions Of Sclumentioning
confidence: 99%